Assessing government spending efficiency and explaining inefficiency scores: DEA-bootstrap analysis in the case of Saudi Arabia - Mohamed Nejib Ouertani; Nader Naifar; Hedi Ben Haddad (Cogent Economics & Finance, 2018)
The recent Saudi Arabia's 'Vision 2030' including the National Transformation Plan has renewed the debate on the efficiency of government spending. The aim of this paper was twofold. First, to measure the relative efficiency of Saudi Arabia's public spending over the period 1988-2013 using non-parametric approach. Second, to explain the inefficiency scores using a DEA-Bootstrap analysis by incorporating environmental variables. The empirical results show that, on average, the public spending is inefficient, implying that Saudi Arabia can improve their performance on health, education and infrastructure without increasing spending. The empirical explanation of the inefficiency scores using a DEA-Bootstrap analysis shows that the unemployment and broad money negatively impact government expenditure mainly in the case of infrastructure and health. Our findings can be useful for policymakers in order to set out a structural adjustment plan to improve the efficiency level for education, health and infrastructure expenditures.
Keywords: 330; Statistics for Business; Finance & Economics; Middle East Economics; Economics; Political Economy